A Survey on the Potential of CF3I Gas as an Alternative for SF6 - Kamarudin, M. S.; Albano, M.; Coventry, P.; Harid, N.; Haddad, A. (2011)
Sulphur hexafluoride (SF6) has been widely used as an insulator in gas-insulated switchgear (GIS) applications. But due to the fact that it is a greenhouse gas, many researchers have been trying to find alternative solutions for it. Furthermore, SF6 produces highly toxic and corrosive substances when it is subjected to electrical discharges. Trifluoroiodomethane (CF3I) has recently been regarded as a candidate for replacing SF6. CF3I has been used as a fire suppressor and now many investigations have been carried out throughout the world to assess its capability in high voltage applications. This paper surveys this previous work and identifies some of the properties which are relevant to high voltage applications.